Many-objective optimization of shell and tube heat exchanger. (June 2017) - Raja, Bansi D.; Jhala, R.L.; Patel, Vivek
Highlights: Many-objective optimization of shell and tube heat exchanger is investigated. MOHTS algorithm is introduced and applied to obtain a set of Pareto points. Comparative results of many-objective and multi-objectives are presented. Relationship of design variables in many & multi objective optimization are presented. Optimum solution is selected by using decision making approaches. Abstract: This paper presents a rigorous investigation of many-objective (four-objective) optimization of shell and tube heat exchangers. Many-objective optimization problem is formed by considering maximization of effectiveness and minimization of total cost, pressure drop and number of entropy generation units of heat exchanger. Multi-objective heat transfer search (MOHTS) algorithm is proposed and applied to obtain a set of Pareto-optimal points. Many objective optimization results form a solution in a four dimensional hyper objective space and for visualization it is represented on a two dimension objective space. Thus, results of four-objective optimization are represented by six Pareto fronts in two dimension objective space. These six Pareto fronts are compared with their corresponding two-objective Pareto fronts. Different decision making approaches that include LINMAP, TOPSIS and fuzzy are used to select the final optimal solution from the Pareto optimal set of the many-objective optimization. Finally, to reveal the level of conflict between these objectives, the distribution of each design variables in their allowable range is also shown in two dimensional objective spaces.